The role of midfrontal theta oscillations across the development of cognitive control in preschoolers and school‐age children. Issue 5 (12th February 2020) - Adam, Nicolas; Blaye, Agnès; Gulbinaite, Rasa; Delorme, Arnaud; Farrer, Chloé
Abstract: The development of cognitive control enables children to better resist acting based on distracting information that interferes with the current action. Cognitive control improvement serves different functions that differ in part by the type of interference to resolve. Indeed, resisting to interference at the task‐set level or at the response‐preparation level is, respectively, associated with cognitive flexibility and inhibition. It is, however, unknown whether the same neural mechanism underlies these two functions across development. Studies in adults have revealed the contribution of midfrontal theta (MFT) oscillations in interference resolution. This study investigated whether MFT is involved in the resolution of different types of interference in two age groups identified as corresponding to different latent structures of executive functions. Preschool (4–6 years) and school children (6–8 years) were tested with a task involving interference at the response level and/or the task‐set level while (electroencephalogram) EEG was recorded. Behaviorally, response time and accuracy were affected by task‐set. Both age groups were less accurate when the interference occurred at the task‐set level and only the younger group showed decreased accuracy when interference was presented at the response‐preparation level. Furthermore, MFT power was increased, relative to the baseline, during the resolution of both types of interference and in both age groups. These findings suggest that MFT is involved in immature cognitive control (i.e., preschool and school‐ages), by orchestrating its different cognitive processes, irrespective of the interference to resolve and of the level of cognitive control development (i.e., the degree of differentiation of executive functions). Abstract : Theta oscillatory activity is observed from infancy to adulthood in situations that engage cognitive control. In this article, we show that theta in midfrontal areas supports the engagement of cognitive control for the resolution of different conficts (at the response and task‐set levels) and over distinct developmental periods (the preschool and school ages).